Seed morphometry and NaCl and sucrose effect on germination rates and phytochemicals in sotol (Dasylirion acrotrichum) from the Chihuahua state, Mexico - Valero Galvan, José; Garza-Vallejo, Gerardo Iván; Quiñonez Martínez, Miroslava; González-Fernández, Raquel (Journal of the Professional Association for Cactus Development, 2024)
In Mexico, “sotoles” (Dasylirion spp.) are used to elaborate the “sotol” liquor, handicraft making, and construction materials. These activities have enhanced the probability that sotol populations could decline because plants are extracted directly from their native ecosystems, given no commercial sotol plant species exist. Furthermore, from an ecological point of view, this genus has also been little studied regarding its seed morphology and germination process. The objective of this study was to characterize the morphometry of the D. acrotrichum seeds and to evaluate the effect of different concentrations of NaCl (30, 60, and 90 mM) and sucrose (30, 60, and 90 mM) on seed germination rates, seedling morphology, and the phytochemical content in the seedling leaves under in vitro conditions from plants grown in the Chihuahua State. The exogenous NaCl and sucrose treatments influenced the germination speed index, mean germination time, and mean germination speed. The NaCl treatment impacted the total weight, root weight, and leaf length of seedlings, the content of chlorophyll a, sugar, and phenolics, and the antioxidant activity determined by FRAP. Besides, the sucrose treatment affected the seedling length, the content of chlorophyll a, chlorophyll b, total chlorophyll, and sugars, and the antioxidant activity determined by FRAP and DPPH. These results could provide the guidelines to generate better afforestation programs in the areas affected by the overexploitation of the Dasylirion spp. and new information about the capacity of these species for developing under these types of stress in the natural environment.